2014
DOI: 10.1186/1471-2458-14-150
|View full text |Cite
|
Sign up to set email alerts
|

Associations between socioeconomic, parental and home environment factors and fruit and vegetable consumption of children in grades five and six in British Columbia, Canada

Abstract: BackgroundRegular fruit and vegetable (FV) consumption has been associated with reduced chronic disease risk. Evidence from adults shows a social gradient in FV consumption. Evidence from pre-adolescent children varies and there is little Canadian data. This study assessed the FV intake of school children in British Columbia (BC), Canada to determine whether socio-economic status (SES), parental and the home environment factors were related to FV consumption.MethodsAs part of the BC School Fruit and Vegetable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 39 publications
10
38
0
10
Order By: Relevance
“…Considering that schoolaged children consume over one-third of their daily energy intake at school (3) , the school day contributes meaningfully to total dietary quality of students. Therefore, these findings suggest that there is room for improvement in the schoolday dietary intake of Vancouver students, consistent with previous research on school-aged children in BC (37) and other regions of Canada (38,39) . The present study further revealed that school-day intakes of vegetables and SSB varied significantly with either parent education or food insecurity (or both), suggesting that low SES may contribute to disparities in dietary quality.…”
Section: Discussionsupporting
confidence: 90%
“…Considering that schoolaged children consume over one-third of their daily energy intake at school (3) , the school day contributes meaningfully to total dietary quality of students. Therefore, these findings suggest that there is room for improvement in the schoolday dietary intake of Vancouver students, consistent with previous research on school-aged children in BC (37) and other regions of Canada (38,39) . The present study further revealed that school-day intakes of vegetables and SSB varied significantly with either parent education or food insecurity (or both), suggesting that low SES may contribute to disparities in dietary quality.…”
Section: Discussionsupporting
confidence: 90%
“…Household income and food security status are both commonly used as SES surrogate measures in health studies, and are associated with Canadian FV consumption 18,19 and with each other in Canada. 19 From an epidemiologic perspective, these relationships make it important to only include one of these measures in an etiologic model of fruit juice and drink intake to avoid a biased SES effect estimate.…”
Section: Study Variablesmentioning
confidence: 99%
“…Moreover, adolescents living in food-insecure households are more likely to report poorer quality diets (Kirkpatrick and Tarasuk 2008). However, Canadian studies drawing from smaller, regional samples report weak associations about the role of SES in shaping dietary outcomes for younger children (Attorp et al 2014;Ahmadi et al 2015). No study has compared in-school dietary outcomes across demographic and socioeconomic characteristics in a large nationally representative sample of Canadian children.…”
Section: Introductionmentioning
confidence: 99%